2013
DOI: 10.1002/jsfa.6028
|View full text |Cite
|
Sign up to set email alerts
|

Olive oil quality and ripening in super‐high‐density Arbequina orchard

Abstract: By sampling and monitoring the ripeness index weekly, it would be possible to determine an optimal harvesting time for olives according to the industrial yield and the physicochemical, nutritional and sensory properties of the olive oil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
45
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 42 publications
13
45
2
Order By: Relevance
“…The total phenols of the olive oils belonging the second harvest year were significantly higher than of the olive oils in the first harvest year (P <0.01). Béltran et al, (2005) and Benito et al, (2012) have also reported that there was a difference between years in terms of total phenols.…”
Section: Total Phenolsmentioning
confidence: 94%
See 3 more Smart Citations
“…The total phenols of the olive oils belonging the second harvest year were significantly higher than of the olive oils in the first harvest year (P <0.01). Béltran et al, (2005) and Benito et al, (2012) have also reported that there was a difference between years in terms of total phenols.…”
Section: Total Phenolsmentioning
confidence: 94%
“…Having knowledge about the chemical properties of olive oil allows us to have an idea about its sensory properties and vice versa (Mailer and Beckingham, 2006). The contribution of total phenol contents to the bitterness and pungency of positive sensory properties of olive oil has been shown in many studies (Rotondi et al, 2004;Nieto et al, 2010;Benito et al, 2012;Rivas et al, 2013). Benito et al, (2012) have reported that fruitiness, bitterness and pungency scores increased up to a maximum coinciding with the maximum total phenol content and then decreased.…”
Section: Sensory Profilementioning
confidence: 95%
See 2 more Smart Citations
“…Olive oil is a genuine fruit juice with excellent nutritional, sensory and functional qualities obtained from the fruit of olive trees (Benito et al, 2013). Increasing evidence suggests that olive oil as a food has been associated with a lower incidence of chronic diseases, particularly coronary heart disease, a lower risk of cancer and other bioactive properties including anti-inflammatory, antioxidant, antiarrhythmic and vasodilatory effects (Covas Mi et al, 2006;López-Miranda et al, 2010).…”
Section: Introductionmentioning
confidence: 99%